Q: Why does 2x-3 equals 2x-5 have no solution?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-2 x 5 = -10

4 equals 2x2, 6 equals 2x3

(2x5)-3

If x = -7, then x3 = -343 so that 2x3 = -686 y = 2 then 15 y = 30 So 2x3 + 15y = -686 + 30 = -656

6 and 10 2x3=6 2x5=10 HCF=2 LCM=30

Related questions

6=2x3 10=2x5 so the LCM of 6 and 10 is 2x3x5=30

The order of steps you take in a math problem Parentheses, Exponents, Multiplication, Division, Addition, Subtraction For Example: (2x3)+20-2x5, if you follow pemdas the answer is:16

2x1 is 2 2x2 is 4 2x3 is 6 2x4 is 8 2x5 is 10 2x6 is 12

you would get an even number; 2x1=2 2x3=6 2x5=10

300

-2 x 5 = -10

f(x) = 2x5 + 5x4 - 2x3 - 7x2 -4x - 12 We use the Leading Coefficient Test to determine the graph's end behavior. Because the degree of f(x) is odd (n = 5) and the leading coefficient, 2, is positive, the graph falls to the left and rises to the right.

4 equals 2x2, 6 equals 2x3

Not necessarily.

(2x5)-3

If x = -7, then x3 = -343 so that 2x3 = -686 y = 2 then 15 y = 30 So 2x3 + 15y = -686 + 30 = -656

The multiples of 6 are: 6x1 and 2x3.